Efficacy of Acupuncture and Moxibustion in Alopecia: A Narrative Review - Li, Andraia R.; Andrews, Laura; Hilts, Alexis; Valdebran, Manuel (Frontiers in Medicine, 2022)
Acupuncture is the practice of applying needles to target specific pressures points in the body. Since originating in China, acupuncture has been practiced for thousands of years to treat numerous conditions including chronic pain and mood disorders. Alopecia is a common dermatologic condition associated with psychological distress and decreased quality of life. Although it remains underexplored in western medicine, recent evidence suggests that acupuncture may be efficacious in the treatment of alopecia. In this review, we discuss the available evidence describing the efficacy of acupuncture or moxibustion alone (ACU) and in combination with other traditional and alternative interventions (ACU+TRAD) for hair loss. Additionally, the proposed physiologic mechanisms, targeted acupuncture points, and the benefits and barriers to treatment will be further described. An exploratory search using PubMed, EMBASE and Scopus databases was performed for studies that evaluated the effect of acupuncture and moxibustion on alopecia. In these studies, both ACU and ACU+TRAD were efficacious for numerous etiologies of hair loss including alopecia areata, androgenetic alopecia, and seborrheic alopecia. Given their ability to modulate the immune system, as well as neuronal networks associated with emotional cognition, the most frequently targeted acupoints were ST 36, GV 20 and LR 3. The proposed mechanistic effect is dependent upon disease etiology and is theorized to be twofold: reduction of inflammation and decrease in testosterone levels. The limited side effect profile of acupuncture makes it an advantageous treatment option, however, factors including cost, time, limited access and aversion to needles may serve as barriers to treatment.